PENGAPLIKASIAN AIR PADA PASCA PANEN SAYURAN SAWI DAN PENGARUHNYA TERHADAP LAMA MASA SIMPAN DAN SUSUT BOBOT PADA TANAMAN SAWI - Prana, Reihan Adi; Prabowo, Rendy; Anjarani, Dyah; Khodijah, Nyayu Siti (Enviagro: Jurnal Pertanian dan Lingkungan, 2024)
This research aimed to evaluate the effect of water application to various parts of mustard greens on postharvest weight loss, moisture content, and chlorophyll levels. The study used a Completely Randomized Design (CRD) with four treatments: water applied to leaves, roots, the whole plant, and a control group. Results showed that water application did not significantly impact weight loss, moisture content, or chlorophyll levels. However, watering the roots provided the best results in maintaining plant weight and moisture content. Watering the leaves increased moisture but posed a risk of accelerated decay, while the control group showed the highest weight loss. In conclusion, root watering is the most effective method to maintain postharvest mustard greens quality.